A Comparative Study on the Probability of Diabetes and Psychosocial Deficiency of Badminton Players Youth Category - S. Hosen, Mostafa.; Dakhill Hatem Al-Selmi, Abeer (International Journal of Psychosocial Rehabilitation, 2020)
Many people believe that diabetes appears after a psychological crisis, which is a misconception, but it could be in them before having a crisis or the crisis. But emotion increases the appearance of symptoms, and athletes are at risk of developing diabetes. Hypoglycemia is not unusual for athletes, and during physical activity the sugar level changes in the blood. Therefore, it is important to conduct tests for the measurement of sugar before and immediately after the activity for the purpose of detecting the sharp drop in the sugar level and treating it, and the early detection is necessary to avoid the possibility of diabetes. The concept of psychological immunity in psychology is considered a positive concepts that maintains the balance of the athlete and the non-athlete between him and his materialistic environment and his social environment. The research problem: A comparative study of the possibility of diabetes and psychological immunity for male and female players of badminton in the youth category, and there are several questions branching out of it: To determine the degree of probability of diabetes in male and female players of badminton in the youth category. Conducting a comparison between the two sex categories in the possibility of diabetes and mental health. To identify the relationship between the possibility of diabetes and psychological immunity for male and female players of .The purpose of the research. Is to identify the degree of probability of developing diabetes and the psychological immunity of male and female players of badminton in the youth category, and to identify the differences between the male and the female badminton players in the probability of diabetes and psychological immunity. The research methodology: The researchers used the descriptive approach on a sample of male and female badminton players (2), and a measurement was applied to determine the probability of diabetes prepared by Dr. Nermin Zakaria (0 family medicine specialist) and Dr. Khalid Al-Zayed, head of Al Adn Health Center in the Ministry of Health (Adan Health Center) Kuwait. The test consists of (7) paragraphs, and the measurement of psychological immunity prepared by Kamel Abboud Hussein and Osama Abdul Qader (2016) consists of 39 positions that are displayed to be answered by the male and female players. The researchers concluded that the members of the male sample of players have a degree of psychological immunity, while the female players do not have a degree of psychological immunity. The researchers recommend: the need to apply other psychological standards on the same sample.